Blue light filtered white light induces depression-like responses and temporary spatial learning deficits in rats. Issue 4 (6th February 2018) - Meng, Qinghe; Lian, Yuzheng; Jiang, Jianjun; Wang, Wei; Hou, Xiaohong; Pan, Yao; Chu, Hongqian; Shang, Lanqin; Wei, Xuetao; Hao, Weidong
Abstract : Objectives : Ambient light has a vital impact on mood and cognitive functions. Abstract : Objectives : Ambient light has a vital impact on mood and cognitive functions. Blue light has been previously reported to play a salient role in the antidepressant effect via melanopsin. Whether blue light filtered white light (BFW) affects mood and cognitive functions remains unclear. The present study aimed to investigate whether BFW led to depression-like symptoms and cognitive deficits including spatial learning and memory abilities in rats, and whether they were associated with the light-responsive function in retinal explants. Methods : Male Sprague-Dawley albino rats were randomly divided into 2 groups ( n = 10) and treated with a white light-emitting diode (LED) light source and BFW light source, respectively, under a standard 12 : 12 h L/D condition over 30 days. The sucrose consumption test, forced swim test (FST) and the level of plasma corticosterone (CORT) were employed to evaluate depression-like symptoms in rats. Cognitive functions were assessed by the Morris water maze (MWM) test. A multi-electrode array (MEA) system was utilized to measure electro-retinogram (ERG) responses induced by white or BFW flashes. Results : The effect of BFW over 30 days on depression-like responses in rats was indicated by decreased sucrose consumption in the sucrose consumption test, an increased immobility time in the FST and an elevated level of plasma CORT. BFW led to temporary spatial learning deficits in rats, which was evidenced by prolonged escape latency and swimming distances in the spatial navigation test. However, no changes were observed in the short memory ability of rats treated with BFW. The micro-ERG results showed a delayed implicit time and reduced amplitudes evoked by BFW flashes compared to the white flash group. Conclusions : BFW induces depression-like symptoms and temporary spatial learning deficits in rats, which might be closely related to the impairment of light-evoked output signals in the retina.